The relationship between agility and lower extremity strength in female basketball players - Ali Kerim Yılmaz; Soner Akgün; Esra Korkmaz Salkılıç; Berna Anıl; Enes Akdemir; Burcu Aktaş; Emre Karaduman; Menderes Kabadayı (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background The aim of the study was to investigate the relationship between agility and lower extremity strength in female basketball players. Methods Fifteen females aged 18–24 years (age 20.80 years, height 1.70 cm, weight 67.60 kg and body mass index (BMI) 23.20 kg/m²) participated in the study voluntarily. In the study, 5-0-5 Agility (505), Pro-Agility (PA), T Agility (T-test), T Drill Hop (T) tests were used to determine the agility skills of the participants. To determine the lower extremity strength performance of the participants, concentric/concentric (Con/Con) isokinetic knee extension (Ex) and flexion (Flx) tests at angular velocities of 60, 180, 240 and 300°/sec, 5 different single leg hop tests (SLHT) [single leg hop for distance (SL), triple leg hop for distance (THD), crossover hop for distance (CHD), medial side triple hop for distance (MSTH), 90° medial rotation hop for distance (MRH)] and 3 different one-repetition maximum (1 RM) [leg press (LP), leg extension (LEX) and leg curl (LC)] tests were performed. Results The results of the study showed a moderate, high and excellent negative correlation between SLHTs and agility (p < 0.05). Comparisons of agility and strength parameters on the right (RS) and left (LS) sides showed no significant difference (p > 0.05). In addition, ipsilateral hamstring/quadriceps (H/Q) and bilateral (H/H-Q/Q) strength ratios and limb symmetry indexes (LSI) obtained from the strength results of the subjects were within the normal range. Conclusions As a result, we found a negative relationship between agility and lower extremity functional performance tests in female basketball players. In addition, it can be said that participants not likely to be injured under normal conditions (non-contact) because of the asymmetric strength ratios are within the safe range.